PERAN LEMAK EPIKARDIAL PADA PENYAKIT JANTUNG KORONER STABIL - Ulzim Fajar; Mefri Yanni (Universitas Fort De Kock, 2020)
Visceral fat tissue widely known have endocrine function by secreting Cytokines that provide it function in metabolism of visceral organ such as heart. It function have pivotal role under physiology and patology condition by secreting antiinflamatory cytokines in physiology condition, otherwise proinflammatory cytokines in patology condition. Epicardial fat tissue as regard this function, have more important role to the heart, because it have two advantage than other visceral depots. First, this tissue have same microcirculation provided by small branch of coronary arteries, and second it were not boundary by any structure. Recent studies found that there were correlation between increased epicardial fat depot and coronary artery disease. It seems correlate with this unique structure and function. This literature review focuse on how is the role of epicardial fat tissue in atheroschlerotic process especially in coronary artery.